Effect of n-3 PUFA supplementation at different EPA:DHA ratios on the spontaneously hypertensive obese rat model of the metabolic syndrome. Issue 6 (27th February 2015) - Molinar-Toribio, Eunice; Pérez-Jiménez, Jara; Ramos-Romero, Sara; Romeu, Marta; Giralt, Montserrat; Taltavull, Núria; Muñoz-Cortes, Mònica; Jáuregui, Olga; Méndez, Lucía; Medina, Isabel; Torres, Josep Lluís
Abstract : The increasing incidence of the metabolic syndrome (MetS), a combination of risk factors before the onset of CVD and type 2 diabetes, encourages studies on the role of functional food components such as long-chain n -3 PUFA as preventive agents. In the present study, we explore the effect of EPA and DHA supplementation in different proportions on spontaneously hypertensive obese (SHROB) rats, a model for the MetS in a prediabetic state with mild oxidative stress. SHROB rats were randomised into four groups ( n 7), each supplemented with EPA/DHA at ratios of 1:1, 2:1 and 1:2, or soyabean oil as the control for 13 weeks. The results showed that in all the proportions tested, EPA/DHA supplementation significantly lowered total and LDL-cholesterol concentrations, compared with those of the control group. EPA/DHA supplementation at the ratios of 1:1 and 2:1 significantly decreased inflammation (C-reactive protein levels) and lowered oxidative stress (decreased excretion of urinary isoprostanes), mainly at the ratio of 1:2. The activity of antioxidant enzymes increased in erythrocytes, abdominal fat and kidneys, with magnitudes depending on the EPA:DHA ratio. PUFA mixtures from fish affected different MetS markers of CVD risk factors in SHROB rats, depending on the ratios of EPA/DHA supplementation. The activation of endogenous defence systems may be related to the reduction of inflammation and oxidative stress.